Nutritional Content of Dried Anchorage (Stolephorus sp.) With Blanching Method - Sartina, Sartina; Harianti, Harianti (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
A fishery commodity that is one of the leading commodities for fisheries in Barru Regency is anchovies (Stolephorus sp.). Salted fish is a processed fish that is preserved with the addition of crystal salt. Blanching is a heat process that uses hot water or steam, and this heating generally takes place at a temperature of 85°C. This study aims to determine the nutritional content of dried anchovies (Stolephorus sp.) using the blanching method. This research will be carried out in April 2025. This test was carried out at the Fisheries Product Biochemistry Laboratory of the Pangkajene and Islands State Agricultural Polytechnic. This research method uses experimental laboratories with two treatments and 3 repetitions. Sample A (blanching method), sample B (without blanching method), analysis data using the Anova test. The results showed that the dry anchovy blanching method improved the chemical quality of dried anchovies, where the value of moisture content (A 31.93%), ash content (16.34%), and protein content (72.50%) was higher and had a real effect on the blanching method (P<0.05). In conclusion, dried anchovies blanching method affects chemical quality